Respuesta :
First you should distribute the left side
8−2(3−x)=4x+6
8 - 6 +2x = 4x +6
2 + 2x = 4x + 6
-4x -4x
2 - 2x = 6
-2 -2
-2x = 4 Divide both sides by -2
x = -2
8−2(3−x)=4x+6
8 - 6 +2x = 4x +6
2 + 2x = 4x + 6
-4x -4x
2 - 2x = 6
-2 -2
-2x = 4 Divide both sides by -2
x = -2
Let's solve your equation step-by-step.8−2(3−x)=4x+6Step 1: Simplify both sides of the equation.8−2(3−x)=4x+68+(−2)(3)+(−2)(−x)=4x+6(Distribute)8+−6+2x=4x+6(2x)+(8+−6)=4x+6(Combine Like Terms)2x+2=4x+62x+2=4x+6Step 2: Subtract 4x from both sides.2x+2−4x=4x+6−4x−2x+2=6Step 3: Subtract 2 from both sides.−2x+2−2=6−2−2x=4Step 4: Divide both sides by -2.−2x−2=4−2x=−2Answer:x=−2